If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + -1) + -3 = 25 + 4x Reorder the terms: 5(-1 + 3x) + -3 = 25 + 4x (-1 * 5 + 3x * 5) + -3 = 25 + 4x (-5 + 15x) + -3 = 25 + 4x Reorder the terms: -5 + -3 + 15x = 25 + 4x Combine like terms: -5 + -3 = -8 -8 + 15x = 25 + 4x Solving -8 + 15x = 25 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -8 + 15x + -4x = 25 + 4x + -4x Combine like terms: 15x + -4x = 11x -8 + 11x = 25 + 4x + -4x Combine like terms: 4x + -4x = 0 -8 + 11x = 25 + 0 -8 + 11x = 25 Add '8' to each side of the equation. -8 + 8 + 11x = 25 + 8 Combine like terms: -8 + 8 = 0 0 + 11x = 25 + 8 11x = 25 + 8 Combine like terms: 25 + 8 = 33 11x = 33 Divide each side by '11'. x = 3 Simplifying x = 3
| z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 | | 3(4y+5)=51 | | 6(2g-5)=-6 | | x^2+9=6x | | 8x+16=2x+106 | | 2y+10=5y-4 | | 14x^2=0 | | 110-5x=22x+20 | | x(x+7)=15x-21 | | 21=1-5p | | 5=3+8b | | 11-10x=85-24x | | 10-2y=y+8 | | 6x*x+35x+48=x | | 12x-x^2=0 | | 4(x-2)-8x=3(1-x)-9 | | 6x+35x+48=8 | | -108-8x=10x+18 | | 47-6x=12x+19 |